2020
DOI: 10.1111/jfd.13137
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and genotypic characterization of Streptococcus spp. isolated from tilapia (Oreochromis spp.) cultured in river‐based cage and earthen ponds in Northern Thailand

Abstract: Streptococcus spp. are major pathogenic bacteria associated with massive mortality in tilapia. This study investigated the phenotypic and genotypic characterization of Streptococcus agalactiae (GBS) and Streptococcus iniae (S. iniae) isolated from tilapia in river-based floating cage and earthen pond farms in northern Thailand. Isolates were identified by biochemical and molecular analyses. Capsular typing, enterobacterial repetitive intergenic consensus polymerase chain reaction and multilocus sequence typing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 31 publications
3
8
0
Order By: Relevance
“…Wastewater and pond water can be reservoirs of GBS [45,46] and exposure of aquatic animals via contaminated surface water has been described on multiple occasions [17,47]. Interestingly, ST283 was commonly found in river cage-based tilapia farms in Thailand but not in earthen pond systems [48]. There is no evidence yet of ST283 in cage-based tilapia farms along the Perfume River.…”
Section: Discussionmentioning
confidence: 99%
“…Wastewater and pond water can be reservoirs of GBS [45,46] and exposure of aquatic animals via contaminated surface water has been described on multiple occasions [17,47]. Interestingly, ST283 was commonly found in river cage-based tilapia farms in Thailand but not in earthen pond systems [48]. There is no evidence yet of ST283 in cage-based tilapia farms along the Perfume River.…”
Section: Discussionmentioning
confidence: 99%
“…Based on our research on S. agalactiae characterization, we could isolate 2 major serotypes, serotype Ia and serotype III, that caused disease in tilapia, which was similar to the surveillance in other countries in SE Asia such as Malaysia [ 17 , 21 , 22 , 37 , 38 , 39 ]. Based on our findings, both serotypes showed similar distribution throughout Thailand during 2012–2014; however, it was found that serotype III exhibited higher virulence than serotype Ia [ 21 ].…”
Section: Discussionmentioning
confidence: 55%
“…The outbreaks of streptococcosis have been related to environmental factors, including warm water temperatures, increased ammonia levels, and low dissolved oxygen [ 11 ]. S. agalactiae infections in tilapia have been reported in global aquaculture in different continents, especially Asia, including Thailand [ 17 , 18 , 19 , 20 , 21 , 22 ], Malaysia [ 23 , 24 , 25 , 26 , 27 ], Indonesia [ 28 , 29 ], Philippines [ 30 ], and China [ 31 , 32 , 33 , 34 ]. Importantly, the emergence of streptococcosis disease can take place anytime during tilapia farming, which may lead to the risk of disease distribution and loss of tilapia production if disease prevention and control are not well managed.…”
Section: Introductionmentioning
confidence: 99%
“…(Dong et al., 2017; Raj et al., 2019), Streptococcus spp. (Chideroli et al., 2017; Niu et al., 2020), Flavobacterium spp. (Dong et al., 2015), Edwardsiella spp.…”
Section: Introductionmentioning
confidence: 99%